1987
DOI: 10.1002/j.1556-6978.1987.tb00727.x
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Evaluating Supervision Effectiveness

Abstract: The authors attempt to bridge the gap between the research literature on supervision and its application to evaluating individual supervisor effectiveness. A conceptual framework is presented for making decisions about evaluation. In this framework the decision maker is directed to consider three issues-the purpose of evaluation, the developmental stage of the counselor, and the focus of evaluation-in selecting measures of' effectiveness. Within this context, some promising measures of supervision effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Findings indicated that the attractive and interpersonally sensitive styles influenced satisfaction with supervision, whereas the task-oriented style influenced supervisees' perceived self-efficacy. Although supervisors may have their preferred styles of supervision, the findings of this study and previous research (Galassi & Trent, 1987) suggest that it would benefit supervisors to adopt varied styles in supervision.…”
Section: Discussionmentioning
confidence: 58%
“…Findings indicated that the attractive and interpersonally sensitive styles influenced satisfaction with supervision, whereas the task-oriented style influenced supervisees' perceived self-efficacy. Although supervisors may have their preferred styles of supervision, the findings of this study and previous research (Galassi & Trent, 1987) suggest that it would benefit supervisors to adopt varied styles in supervision.…”
Section: Discussionmentioning
confidence: 58%
“…Supervisors are the primary source of evaluations of counseling performance (Galassi & Trent, 1987), and rating scales are the predominant method of evaluation (Fuqua, Newman, Scott, & Gade, 1986). It is becoming increasingly clear, however, that evaluating coun-…”
Section: Amentioning
confidence: 99%
“…417-418). However, to date, the developmental models have not developed to the point of identifying the specific skills and interventions necessary to best facilitate counselor cognitive development at each stage of the process (Etringer, Hillerbrand, & Claiborn, 1995;Galassi & Trent, 1987). Developmental models stress the importance of matching the supervisor's behavior to the developmental needs ofthe supervisee (Littrell, Lee-Borden, & Lorenz, 1979).…”
mentioning
confidence: 99%